Tuning the hydrophobic properties of silica particles by surface silanization using mixed self-assembled monolayers - Kulkami, Sneha A.; Ogale, Satishchandra B.; Vijayamohanan, Kunjukrishanan P. (Journal of Colloid and Interface Science, 2008)
Here we describe a novel method of preparing hydrophobic silica particles (100-150 nm; water contact angle of dropcasted film ranging from 60 degrees to 168 degrees) by surface functionalization using different alkyltrichlorosilanes. During their preparation, the molecular surface roughness is also concurrently engineered facilitating a change in both the surface chemical composition and the geometrical microstructure to generate hierarchical structures. The water contact angle has been measured on drop-cast film surface. The enhancement in the water contact angle on 3D (curved) SAMs in comparison to that on 2D (planar) surface is discussed using the Cassie-Baxter equation. These silica particles can be utilized for many potential applications including selective adsorbents and catalysts, chromatographic supports and separators in microfluidic devices. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: alkyltrichlorosilane; silanization; silica particles; superhydrophobicity